Acoustics of porous composites. (1st September 2021) - Venegas, Rodolfo; Zieliński, Tomasz G.; Núñez, Gabriel; Bécot, François-Xavier
Abstract: Acoustic wave propagation in porous composites is investigated in this paper. The two-scale asymptotic homogenisation method is used to obtain the macroscopic description of sound propagation in such composites. The developed theory is both exemplified by introducing analytical models for the effective acoustical properties of porous composites with canonical inclusion patterns (i.e. a porous matrix with a periodic array of cylindrical or spherical inclusions) and validated by comparing the models predictions with the results of direct finite-element simulations and experimental testing, showing good agreement in all cases. It is concluded that the developed theory correctly captures the acoustic interaction between the constituents of the porous composite and elucidates the physical mechanisms underlying the dissipation of sound energy in such composites. These correspond to classical visco-thermal dissipation in the porous constituents, together with, for the case of composites made from constituents characterised by highly contrasted permeabilities, pressure diffusion which provides additional and tunable sound energy dissipation. In addition, this work determines the conditions for which a rigidly-backed porous composite layer can present improved sound absorption performance in comparison with that of layers made from their individual constituents. Hence, the presented results are expected to guide the rational design of porous composites with superior acoustic performance. Highlights: Adding inclusions to porous layers can improve their acoustic performance. Theory for porous acoustic composites rigorously developed and numerically verified. Rules for designing the size, pattern, and material of the inclusions provided. Experimental validation for composites with weak permeability contrast.